Numerical Analysis of Non-Constant Discounting with an Application to Renewable Resource Management - FUJII, Tomoki (Institutional Knowledge at Singapore Management University, 2006)
The possibility of non-constant discounting is important in environmental and resource management problems where current decisions affect welfare in the far-distant future, as with climate change. The difficulty of analyzing models with non-constant discounting limits their application. We describe and provide software to implement an algorithm to numerically obtain a Markov Perfect Equilibrium for an optimal control problem with non-constant discounting. The software is available online. We illustrate the approach by studying welfare and observational equivalence for a particular renewable resource management problem.